Pengembangan Video Pembelajaran Untuk Siswa Kelas X Pelajaran Dasar - Dasar Teknik Mesin Pada Materi Pengelasan SMAW Jurusan Teknik Mesin SMK Negeri 3 Surabaya - Pambudi, Rizdana Galih; yunus, yunus (Journal of Vocational and Technical Education (JVTE), 2023)
Based on observations at the introduction of the school field, information was obtained in the subject of basic mechanical engineering SMAW welding material, students had difficulty understanding the material due to the lack of learning support facilities that could motivate students. In addition, learning methods are still conventional and abstract in nature affecting learning outcomes. This study aims to develop a learning video for SMAW welding material that is feasible to use so that it is expected to be able to increase the response and effectiveness of learning outcomes of class X students of Machining Engineering at SMK Negeri 3 Surabaya. This type of research is Research and Development (RnD) research with the 4D development model (Define, Design, Develop, Disseminate). This study was conducted to assess the effectiveness of learning outcomes using the one group pre-test post-test design method. Data collection techniques using validation sheets, pre-test post-test sheets and student response sheets. The results of this study obtained 95.83% feasibility for material experts while 86.97% for media experts and 94.16% media experts. including the category very feasible. The effectiveness of learning media was obtained at 0.7303, including in the high category. The response of students was obtained at 85.16%, including in the very strong category. So it is concluded that the learning video can be used as a support for learning SMAW welding material. Keywords: Learning Media, Learning Video, 4D Model, One Group Pre-Test Post-Test Design.